Characterization of enzyme produced from pseudomonas putida for BTX (benzene, toluene & xylene) treatment in petrochemical industry wastewater system - Azoddein, Abdul Aziz Mohd; Abu Seman, M. N.; Said, Nurdin; Nik Meriam, Nik Sulaiman (2016)
One of the big challenges in petrochemical industries is waste management. Currently, huge money was spending on the disposal of the waste. Industries are trying hard to find an alternative method to reduce the cost and improve the effectiveness of current waste management including treatment efficiency. Most of petrochemical wastes are containing benzene, toluene and xylene (BTX) which are very harmful to environment and living organisms. Common method used to separate the BTX from the waste are by using liquid-liquid extraction and stripping process. One of the alternative to treat BTX is biological treatment method that used the natural capability of microorganisms to degrade to less harmful product is been applied. Some of examples are Pseudomonas Putida. (P. putida), Rhizobium, and Agrobacterium. P. putida is selected in this study for the biological treatment of BTX in petrochemical wastewater because it can produce an enzyme that has the capability of breakdown the aromatic hydrocarbon to carbon dioxide (CO2) and water (H2O). The main objective of this study is to produce and extract the enzymes produce, characterised the enzymes. This study also to investigate the effect of different concentration on the treatment as well as the growth of the bacteria. The enzyme is purified using salt precipitation and analysed using SDS-PAGE technique. UV-Vis is used to study the growth of the bacteria in the culture stock by measuring its optical density. The concentration of BTX was varied to determine the effect of the concentration on the percentage removal and the growth of P. putida. Enzymes detected or purified in this study was benzene reductase. Other expected enzymes were not able to be purified or analysed. It was found that in this experimental study, the removal of benzene is at 74% to 80%. The removal of toluene is at 62% to 75%. The removal of xylene is at 23% to 42%. Increasing the concentration of contaminants will reduce the removal capabilities.